2022
DOI: 10.1186/s12885-021-09064-0
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in glycolytic/cholesterogenic gene expression is associated with bladder cancer prognosis and immune cell infiltration

Abstract: Background Oncogenic metabolic reprogramming contributes to tumor growth and immune evasion. The intertumoral metabolic heterogeneity and interaction of distinct metabolic pathways may determine patient outcomes. In this study, we aim to determine the clinical and immunological significance of metabolic subtypes according to the expression levels of genes related to glycolysis and cholesterol-synthesis in bladder cancer (BCa). Methods Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…It is conceivable that the stratified model, which first stratified patients into subgroups, and then applied individual based risk stratification, can be used to predict biologically relevant clinical outcomes. The concept of “subtype specific” biomarkers has been successfully applied to improve the prognosis of many kinds of cancers ( Hu et al, 2021 ; Ahearn et al, 2022 ; Zhang et al, 2022 ). Therefore, integrating subtype analysis and individual based models may be a promising method to develop clinically relevant biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that the stratified model, which first stratified patients into subgroups, and then applied individual based risk stratification, can be used to predict biologically relevant clinical outcomes. The concept of “subtype specific” biomarkers has been successfully applied to improve the prognosis of many kinds of cancers ( Hu et al, 2021 ; Ahearn et al, 2022 ; Zhang et al, 2022 ). Therefore, integrating subtype analysis and individual based models may be a promising method to develop clinically relevant biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…LRP1B role as a candidate tumor suppressor also for bladder cancer has been proposed several years ago [ 25 ]; however, its function still remains to be fully elucidated. A lower frequency of its copy-number deletions was newly associated with a specific subtype of bladder cancer (quiescent type) that exhibited the best overall survival [ 26 ]. Our TCGA analysis confirmed its crucial role, for the first time linked to short-term prognosis (1-year survival).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular Subtypes. Previous studies have found a relationship between glycolytic/cholesterol metabolism and immune infiltration [35,36]. erefore, we compared the distribution of our molecular subtypes to the previous immune subtypes.…”
Section: Comparing Our Molecular Subtypes and Existing Immunementioning
confidence: 99%